Generation of high affinity ICAM-1-specific nanobodies and evaluation of their suitability for allergy treatment - Zettl, Ines; Ivanova, Tatiana; Zghaebi, Mohammed; Rutovskaya, Marina V.; Ellinger, Isabella; Goryainova, Oksana; Kollárová, Jessica; Villazala-Merino, Sergio; Lupinek, Christian; Weichwald, Christina; Drescher, Anja; Eckl-Dorna, Julia; et al. (Frontiers in Immunology, 2022)
The nasal cavity is an important site of allergen entry. Hence, it represents an organ where trans-epithelial allergen penetration and subsequent IgE-mediated allergic inflammation can potentially be inhibited. Intercellular adhesion molecule 1 (ICAM-1) is highly expressed on the surface of respiratory epithelial cells in allergic patients. It was identified as a promising target to immobilize antibody conjugates bispecific for ICAM-1 and allergens and thereby block allergen entry. We have previously characterized a nanobody specific for the major birch pollen allergen Bet v 1 and here we report the generation and characterization of ICAM-1-specific nanobodies. Nanobodies were obtained from a camel immunized with ICAM-1 and a high affinity binder was selected after phage display (Nb44). Nb44 was expressed as recombinant protein containing HA- and His-tags in E. coli and purified via affinity chromatography. SDS-PAGE and Western blot revealed a single band at approximately 20 kDa. Nb44 bound to recombinant ICAM-1 in ELISA, and to ICAM-1 expressed on the human bronchial epithelial cell line 16HBE14o- as determined by flow cytometry. Experiments conducted at 4°C and at 37°C, to mimic physiological conditions, yielded similar percentages (97.2±1.2% and 96.7±1.5% out of total live cells). To confirm and visualize binding, we performed immunofluorescence microscopy. While Texas Red Dextran was rapidly internalized Nb44 remained localized on the cell surface. Additionally, we determined the strength of Nb44 and ICAM-1 interaction using surface plasmon resonance. Nb44 bound ICAM-1 with high affinity (10-10 M) and had slow off-rates (10-4 s-1). In conclusion, our results showed that the selected ICAM-1-specific nanobody bound ICAM-1 with high affinity and was not internalized. Thus, it could be further used to engineer heterodimers with allergen-specific nanobodies in order to develop topical treatments of pollen allergy.